Penyuluhan pada Remaja Tentang Infeksi Menular Seksual di Pulau Kasu, Kelurahan Kasu, Kecamatan Belakang Padang Kota Batam, Provinsi Kepulauan Riau - Erika Fariningsih; Jihan Febiyanti; ‘Aa’isyah Phoebe Putri Ivanny (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Background: During adolescence, a number of changes occur such as sexual, physical, psychological, and social changes that all appear at the same time. One of the health problems that are often faced by young adults is reproductive health problems because during adolescence, puberty will occur, a period of rapid maturation of sexual organs that will affect decision making, sexual behavior and reproductive health so that adolescents will be motivated to explore sexual experiences which if carried out without direction can result in adolescents engaging in sexual activities that can trigger Sexually Transmitted Infections (STIs). Objective: To assess the extent to which counseling for adolescents can have a positive impact in increasing adolescent knowledge about STIs and whether the program is effective in improving understanding and quality of life for adolescents. Community Service Results: There was an increase in subject knowledge before being given health counseling about Sexually Transmitted Infections which was not good with an average score of 75 while subject knowledge after being given health counseling through leaflets and animated videos with a score of 100.